Endothelial cells during craniofacial development: Populating and patterning the head - Asrar, Hiba; Tucker, Abigail S. (Frontiers in Bioengineering and Biotechnology, 2022)
Major organs and tissues require close association with the vasculature during development and for later function. Blood vessels are essential for efficient gas exchange and for providing metabolic sustenance to individual cells, with endothelial cells forming the basic unit of this complex vascular framework. Recent research has revealed novel roles for endothelial cells in mediating tissue morphogenesis and differentiation during development, providing an instructive role to shape the tissues as they form. This highlights the importance of providing a vasculature when constructing tissues and organs for tissue engineering. Studies in various organ systems have identified important signalling pathways crucial for regulating the cross-talk between endothelial cells and their environment. This review will focus on the origin and migration of craniofacial endothelial cells and how these cells influence the development of craniofacial tissues. For this, we will look at research on the interaction with the cranial neural crest, and individual organs such as the salivary glands, teeth, and jaw. Additionally, we will investigate the methods used to understand and manipulate endothelial networks during the development of craniofacial tissues, highlighting recent advances in this area.